'Millennial debt and developing countries : a new kind of debt?' - Enniss-Trotman, Margaret ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Explores the notion of 'millennial debt' held by developing countries. Highlights the primary reasons behind the persuavieness of the external indebtedness problem in the Latin American region at the turn of the new century.